Pre-oviposition factors influencing the fertility and hatchability in Japanese quail - NARAHARI, D; MUJEER, K A; RAJINI, R A (The Indian Journal of Animal Sciences, 2014)
The season of hatch of the Japanese quail eggs had no significant effect on any of the hatchability traits studied. The fertility rate increased in the quail breeders from 8 to 17 weeks of age and reduced gradually thereafter; whereas, the hatchability had started reducing gradually from 8 to 22 weeks of age and remained static thereafter. A 24hr photoperiod to the quail breeders Significantly improved the fertility; but the hatchability was in favour of the 12hr photoperiod. Light in the setter compartment had not improved the hatchability; but shortened the incubation period by 7. 7hr. Breeder male: female ratios, wider than 1.2 significantly reduced the fertility and hatchability and increased the embryonic mortality. The fertility and hatchability rates were higher in the cage system; with proportionate reduction in the early embryonic mortality. Eggs with light greyish blue shells had lower rate of fertility than brown colour eggs; but the hatchabiLty and embryonic mortality were comparable between eggs with different shell colour patterns. For optimal fertility and hatchability, the Japanese quail breeder diet should contain 50 mg of vitamin E and 13 mg of riboflavin/kg diet. Eggs laid during night time (18-6hr) had better hatchability; with proportionate reduction in early embryonic mortality; but had no influence on fertility.